Acute Rupture of the Plantar Fascia in a Soccer Player - Costa, Diogo (2023)
Acute rupture of the plantar fascia is a rare but potentially debilitating injury in athletes, particularly those involved in running and jumping sports. Early recognition and prompt treatment are crucial for a successful recovery and return to play. Conservative treatment, including rest, immobilization, and physical therapy, may be effective in most cases, while surgical intervention may be required in those that are nonresponsive to conservative treatment. We report a case of plantar fascia rupture in a 22-year-old male semi-professional football player who presented with sudden severe pain in the sole of his right foot during a match, followed by a popping sensation and inability to weight bear. The athlete was healthy and had no history of previous injury in the right foot. MRI confirmed a complete rupture of the plantar fascia. The player was treated conservatively and underwent a rehabilitation program. The player returned to full competition after nine weeks, with no limitations